Stressed interbank markets: evidence from the European financial and sovereign debt crisis - Juan Carlos Frutos; Carlos Garcia-de-Andoain; Florian Heider; Patrick Papsdorf (European Central Bank (ECB), 2016)
This paper documents stress in the unsecured overnight interbank market in the euro area over the course of the financial and sovereign debt crisis in Europe. We find that stress i) leads some banks to borrow in the market at rates that are higher than the rate of the marginal lending facility of the ECB, ii) leads to less cross-border transactions and contributes to the fragmentation of the euro area money market. A triple-difference estimate shows that the borrowing of banks in the periphery from banks in the core almost disappears in the second half of 2011. Domestic borrowing, however, replaces the loss of cross-border borrowing. Our findings document the severe malfunctioning of the market for liquidity caused by asymmetric information problems in crisis times. We exploit euro area payments data to construct a novel dataset of interbank lending and borrowing. We verify the validity of our approach using the post-trading structure MID, maintained at Banco de Espa\~na. Based on our results, we conclude that MID is a very high quality source of Spanish interbank market data for research and policy purposes.
Keywords: G01; G21; E58; F36; 330; European sovereign debt crisis; financial crisis; Furfine algorithm; interbank markets; payment systems